Tindak Pidana Kekerasan Dalam Rumah Tanga Berdasarkan Perspektif Sosiologi Hukum - Muhammad Rifaldi; Oci Senjaya (Jurnal Ilmiah Wahana Pendidikan, 2022)
Domestic violence is a widespread phenomenon in people's lives. Domestic violence often results from a variety of factors, including different perspectives and economic problems. Domestic violence (DRT) usually occurs between women / wives and can be experienced by anyone, anywhere, anytime. From a sociological point of view, this study shows that domestic violence is a type of crime that pervades without boundaries of ethnicity, beliefs, or social status. Domestic violence was originally a privacy issue, but it has been regarded as a public interest and criminal act because the impact of all types of violence on physical, sexual and psychological victims is severe and serious. In Indonesia itself, the patriarchal cultural perspective predominates. A culture that supports men and their pedigree as household policy makers. Law No. 23 of 2004 prohibits domestic violence against any person in the household, regardless of the form of physical violence, psychological violence, sexual violence, or domestic violence. It states that there is. It is also considered a crime against humanity based on human rights principles.